Dynamic Procedures and Incentives in Public Good Economies - Chander, Parkash (Econometrica, 1993)
This paper considers economies involving one public good, one private good, and convex technology and proposes an informationally decentralized dynamic nontatonnement procedure that converges in general from the initial endowments to an allocation in the core. The procedure may be seen as enunciating a plausible method of cooperation among the agents for achieving an optimal provision of a public good and an equitable sharing of its cost. The viewpoint of noncooperative game theory is also considered and it is shown that there exists a trade-off between the requirements of local incentive compatibility and equitable cost sharing. Copyright 1993 by The Econometric Society.